Gingiva-Derived Mesenchymal Stem Cells: Potential Application in Tissue Engineering and Regenerative Medicine - A Comprehensive Review - Kim, Dane; Lee, Alisa E.; Xu, Qilin; Zhang, Qunzhou; Le, Anh D. (Frontiers in Immunology, 2021)
A unique subpopulation of mesenchymal stem cells (MSCs) has been isolated and characterized from human gingival tissues (GMSCs). Similar to MSCs derived from other sources of tissues, e.g. bone marrow, adipose or umbilical cord, GMSCs also possess multipotent differentiation capacities and potent immunomodulatory effects on both innate and adaptive immune cells through the secretion of various types of bioactive factors with immunosuppressive and anti-inflammatory functions. Uniquely, GMSCs are highly proliferative and have the propensity to differentiate into neural cell lineages due to the neural crest-origin. These properties have endowed GMSCs with potent regenerative and therapeutic potentials in various preclinical models of human disorders, particularly, some inflammatory and autoimmune diseases, skin diseases, oral and maxillofacial disorders, and peripheral nerve injuries. All types of cells release extracellular vesicles (EVs), including exosomes, that play critical roles in cell-cell communication through their cargos containing a variety of bioactive molecules, such as proteins, nucleic acids, and lipids. Like EVs released by other sources of MSCs, GMSC-derived EVs have been shown to possess similar biological functions and therapeutic effects on several preclinical diseases models as GMSCs, thus representing a promising cell-free platform for regenerative therapy. Taken together, due to the easily accessibility and less morbidity of harvesting gingival tissues as well as the potent immunomodulatory and anti-inflammatory functions, GMSCs represent a unique source of MSCs of a neural crest-origin for potential application in tissue engineering and regenerative therapy.